1985
DOI: 10.1063/1.95733
|View full text |Cite
|
Sign up to set email alerts
|

X-ray double crystal diffraction study of porous silicon

Abstract: Depending on the dopant concentration, two distinct types of porous silicon can be formed during the anodization of silicon in hydrofluoric acid. A range of samples of both types of porous silicon has been investigated using x-ray double crystal diffraction techniques. The crystal lattice of porous silicon is found to be tetragonally distorted. In the plane of the substrate, the interplanar spacing of the porous film is identical to that of the substrate but is increased in the direction normal to it. The incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
3

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(34 citation statements)
references
References 4 publications
2
29
0
3
Order By: Relevance
“…8peak at 2θ = 28.38° oriented only along the (111) direction is observed confirming the monocrystalline structure of the Si layer which belongs to the (111) reflecting plane of Si of cubic structure (according to ICDD N 1997and 2011 JCPDS) while Porous silicon layer which belongs to the (211) orientation. The increase in lattice constant has also been observed in porous silicon by Young et al, and suggested that the increase in lattice constant arises from stress induced by growth of a native oxide on the surface on the pore structures [7]. The average diameter of crystallites resulting of the broadening in a spectrum at 20 mA/cm 2 etching current density was 73nm.…”
Section: Resultsmentioning
confidence: 68%
“…8peak at 2θ = 28.38° oriented only along the (111) direction is observed confirming the monocrystalline structure of the Si layer which belongs to the (111) reflecting plane of Si of cubic structure (according to ICDD N 1997and 2011 JCPDS) while Porous silicon layer which belongs to the (211) orientation. The increase in lattice constant has also been observed in porous silicon by Young et al, and suggested that the increase in lattice constant arises from stress induced by growth of a native oxide on the surface on the pore structures [7]. The average diameter of crystallites resulting of the broadening in a spectrum at 20 mA/cm 2 etching current density was 73nm.…”
Section: Resultsmentioning
confidence: 68%
“…4 For an as-formed PS sample, strain depends on various parameters, the most important being the porosity of the PS layer, the type and the level of doping of the silicon substrate. 5,6 Owing to lattice mismatch with bulk Si, a PS layer is expected to be under compressive stress 7 when attached to the Si substrate. Additionally, owing to the large internal surface, the strain is very sensitive to oxidation, to the presence of a fluid or to impregnation with various substances.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the accurate analysis of the composition and morphology of PS is of great importance to precisely control its behavior. Up to now, many studies about the structure of PS by the use of different techniques such as transmission electron microscopy (TEM) [3][4][5], X-ray diffraction (XRD) [6][7][8] and Raman spectroscopy [9], have been reported. In particular, we have previously investigated in detail the structure of PS by means of high-resolution transmission electron microscopy (HRTEM) and digital image processing [10,11].…”
Section: Introductionmentioning
confidence: 99%